2013
DOI: 10.1007/s12291-013-0350-z
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Dimethylnitrosamine-Induced Liver Injury and Fibrosis by Supplementation of Anabasis articulata Extract in Rats

Abstract: Anabasis articulata (Forssk) Moq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Preventing the formation of hydroxyl radical protects the cells from oxidative stress‐induced cellular damage . In numerous previous studies, silymarin has been used as a positive control and it has been found that silymarin treatment restores the elevated NO and iNOS levels caused by liver injury to normal levels. The present study obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing the formation of hydroxyl radical protects the cells from oxidative stress‐induced cellular damage . In numerous previous studies, silymarin has been used as a positive control and it has been found that silymarin treatment restores the elevated NO and iNOS levels caused by liver injury to normal levels. The present study obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The granuloma’s diameter was calculated as the mean of its vertical and horizontal diameters. For each mice group, the mean granuloma diameter (MGD) was calculated [ 52 , 53 ]. Lesion counts between 50 and 100 µm were considered.…”
Section: Methodsmentioning
confidence: 99%
“…It is used alone in decoctions or mixed with other medicinal plants [34]. It is regarded for its larvicidal qualities in addition to its antidiabetic effects [35] and also has hepatoprotective and therapeutic effects against liver damage [36]. Anabasis aphylla (haze shrub) has important ecological, economic, and medicinal value [37].…”
Section: Traditional Usementioning
confidence: 99%